Systematic expression analysis of WEE family kinases reveals the importance of PKMYT1 in breast carcinogenesis. (14th December 2019) - Liu, Yu; Qi, Jian; Dou, Zhen; Hu, Jiliang; Lu, Li; Dai, Haiming; Wang, Hongzhi; Yang, Wulin
Abstract: Objectives: Many cancer cells depend on G2 checkpoint mechanism regulated by WEE family kinases to maintain genomic integrity. The PKMYT1 gene, as a member of WEE family kinases, participates in G2 checkpoint surveillance and probably links with tumorigenesis, but its role in breast cancer remains largely unclear. Materials and Methods: In this study, we used a set of bioinformatic tools to jointly analyse the expression of WEE family kinases and investigate the prognostic value of PKMYT1 in breast cancer. Results: The results indicated that PKMYT1 is the only frequently overexpressed member of WEE family kinases in breast cancer. KM plotter data suggests that abnormally high expression of PKMYT1 predicts poor prognosis, especially for some subtypes, such as luminal A/B and triple‐negative (TNBC) types. Moreover, the up‐regulation of PKMYT1 was associated with HER2‐positive (HER2+), basal‐like (Basal‐like), TNBC statuses and increased classifications of Scarff, Bloom and Richardson (SBR). Co‐expression analysis showed PKMYT1 has a strong positive correlation with Polo‐like kinase 1 (PLK1), implying they may cooperate in regulating cancer cell proliferation by synchronizing rapid cell cycle with high quality of genome maintenance. Conclusions: Collectively, this study demonstrates that overexpression of PKMYT1 is always found in breast cancer and predicts unfavourable prognosis, implicating it as an appealing therapeutic target for breast carcinoma.